Disparitas Fiskal Daerah Antara Kebutuhan dan Kapasitas Kabupaten Sumbawa Tahun 2019-2024 - Safira Aisya Rifa; Himawan Sutanto; Ali Akbar Hidayat (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the fiscal disparity between fiscal capacity and fiscal needs in Sumbawa Regency from 2019-2024. The method used is descriptive quantitative with secondary data from the BPKAD and BPS of Sumbawa Regency, including data on GRDP, APBD, population, and the number of sub-districts. The research variables include fiscal capacity, fiscal independence ratio, fiscal dependency ratio, degree of fiscal decentralization, and fiscal needs. The results show that Sumbawa Regency's fiscal capacity is relatively low with a ratio of 1.035 and an average fiscal independence ratio of only 15%. Conversely, the fiscal dependency ratio is high at 85%. Fiscal needs increase significantly along with population growth and public spending: regional spending increases from IDR 1.834 trillion to IDR 2.033 trillion in 2024, with percapita expenditure increasing from IDR 1.098 million to IDR 1.288 million. Therefore, Sumbawa Regency needs to streamline operational spending, especially employee spending, by adjusting the policy of cutting TKD by around 24.8% in the 2026 Draft State Budget. The regional government must explore the real potential of PAD based on Sumbawa's leading sectors with specific and measurable strategies based on that potential, rather than simply following targets, in order to support sustainable fiscal policies in the region.